Do peixe com farinha à macarronada com frango: uma análise das transformações na rede urbana no Alto Solimões pela perspectiva dos padrões alimentares. - Tatiana Schor (Confins, 2017)
The changes and continuities in eating patterns are indicative of complex social and environmental change. The transformation from a diet based on products gathered, fished, hunted, planted or even purchased locally for a “supermarket diet”, indicates the passage of a traditional diet to a more modern diet. This transformation is an interesting indicator of modernization processes. The analysis of these changes allows us to understand diverse processes such as urbanization and its effects on social organization and the individual. Eating habits in Brazil, are somewhere between the "traditional" way of obtaining food and a "supermarket diet", which varies from region to region. The theme of food supply in the Amazon should be examined as a matter comprising the demand and supply of food in the cities and the factors that shape the urban network. Referring to demands, we have a process of ongoing urbanization with a strong financial component explained in various social development policies that quickly transform the eating habits of the population. Regarding supply, there is the fact that rural production in the Amazon does not meet the demand of cities. Amazonas State, in Brazil, is heavily dependent on foreign production. This dependence and the fact that access to most of the cities in the state is mainly by boat involves a complex supply network. This network is strongly defined by the hydrological cycle. This article brought new elements to the understanding of economic and alimentary dynamics in the tri-border Brazil-Peru-Colombia, looking at flows of food and local production and their importance in the supply of cities in the region. We conclude that in the context of strong hydrologic vulnerability, to understand the structures of urban supply networks and local production is essential to think about ways of promoting food sovereignty in the region with heavy reliance on food produced outside the region and the lowest levels of social development in Brazil. The results are not conclusive, but strongly indicate the need to innovate both in research and in the frontier areas of urban-economic geography, and its interface with the geography of supply and health.